DAMPAK DEGRADASI LINGKUNGAN PESISIR TERHADAP KONDISI EKONOMI NELAYAN: STUDI KASUS DESA TAKISUNG, DESA KUALA TAMBANGAN, DESA TABANIO - Mustika, Rima (Pusat Penelitian Sumberdaya Pesisir dan Laut, Universitas Maritim Raja Ali Haji, Indonesia, 2017)
Aim of the research were to determine the types of environmental damage and factors that causing it in coastal area of Tanah Laut as well as its impact to economics of fishermen. We used a descriptive method in order to demonstrate the responder perception regarding to the impact of coastal degradation quality. The resident household in Tabanio, Takisung and Kuala Tambangan Village were chosen as the respondents using random sampling approach using Participatory Rural Appraisal and in depth study. To identify type damage of coastal area resources we conducted the field study activity using ball snow method following by further analysis i.e. muster data of factual / primary to analysis comprehensively. Result of the research showed the exploitation of mangrove forest by community for firewood and build a residential, dash against seaboard by waving high, tide of sea water, stricture of river estuary and contamination of territorial water of sea were the main factors of environmental degradation. We noted that the impact of such coastal degradation to societal economic were lowering of society income, changing of work type of living and changing of ownership of farm.